MENELAAH TIGA PANDANGAN TENTANG HAK KEKAYAAN INTELEKTUAL UNTUK MENJEMBATANI REFORMASI KELEMBAGAAN DAN HUKUM DI ERA AI - Rifki Fahrial Zainal; Dharmawan Setyo Noegroho (LPPM Universitas Bhayangkara Surabaya, 2025)
Particularly in the field of intellectual property (IPR) law, the incorporation of artificial intelligence (AI) into contemporary legal and institutional frameworks offers both unprecedented opportunities and formidable obstacles. This essay examines how, to address the consequences of AI-driven innovation, institutional and legal reforms must evolve in tandem. The paper assesses the interplay between AI technologies and IPR systems by examining three key perspectives: institutional coherence, legal adaptability, and technological determinism. To ensure a fair and balanced approach to intellectual property in the AI era, the study emphasizes the need for proactive governance, flexible legal standards, and a cohesive institutional framework. A framework for coordinating institutional and legal reforms that can support rapid technological progress while upholding fundamental notions of fairness and creativity is suggested in the study’s conclusion.